DESIGN AND VALIDITY OF AN E-ASSESSMENT FOUR TIER MULTIPLE CHOICE TO ASSESS SCIENCE LITERACY SKILLS OF SENIOR HIGH SCHOOL STUDENTS - Gunawan, Maulina Suryati; Mufit, Fatni (Department of Physics Universitas Negeri Padang, 2024)
The low level of science literacy in sound and light waves is a problem in education, especially in physics learning. The low science literacy is caused by students' low understanding of concepts. Assessment instruments that specifically assess students' science literacy skills on the concept of sound and light waves are not widely available. This study aims to develop a valid four-level multiple choice e-assessment to assess students' science literacy skills on the concept of sound and light waves. This research is a development/design (R&D) research using the Plomp model. The developed e-assessment was validated by five experts. The data collection instruments used were interview sheets, self-evaluation sheets, and validation sheets. The results of the validity analysis showed that the e-assessment was in the valid category in terms of construction feasibility aspects, content feasibility aspects, display feasibility aspects, and language feasibility aspects. From the validity results with an average value of 0.94, it shows that the four-level multiple choice assessment to assess science literacy skills is declared valid and suitable for use.